Compartilhamento da informação e a gestão de pessoas: reflexões acerca de suas relações e implicações - Rita de Cassia Martins de Oliveira Ventura (2016)
The objective of this work circumscribes in analyze the existing relationship between the model of people management and availability for information sharing. The relevance of this topic is justified by the importance of the information, related to its sharing, has within organizations, besides the relevance of the people, bearers of knowledge, have in the act of sharing and construction of meaning from these information. The information in organizations can be understood as a ballast that supports all flows of decision-making and execution, becoming the sharing of information the key point in this setting, which reinforces the role of the human being as the protagonist of this process. As a methodological design, a descriptive and relational research was carried out through a case study, using a qualitative approach that involved the use of document analysis, semi-structured interviews and focus groups for the data collection process. The empirical context of the research consisted of a financial institution, more precisely a Single Credit Cooperative, with 215 employees comprised of 1 Administrative Center (CAD) and 17 stations of Cooperative Service (PACs) located in the eastern portion of the state of Minas Gerais. In general, the data show significant relationship between the people management model practiced, model Hard (control strategy), and the willingness to information share. Among other findings, the results confirm the findings of related research already completed under of information sharing and point the variable trust as a precondition for the sharing of information, whether personal or organization. This study corroborates the assertions that the people management model adopted preponderantly influences the behavior of the employees involved in the process, giving new meaning to the role of the human being as a thinking being and endowed with interests that can cause them to develop a political behavior using individual strategies of use of information for career development and the achievement of its objectives.